2021
DOI: 10.3390/nano11040842
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Scale and Chip-Scale Transfer Techniques for Functional Devices and Systems: A Review

Abstract: Hetero-integration of functional semiconductor layers and devices has received strong research interest from both academia and industry. While conventional techniques such as pick-and-place and wafer bonding can partially address this challenge, a variety of new layer transfer and chip-scale transfer technologies have been developed. In this review, we summarize such transfer techniques for heterogeneous integration of ultrathin semiconductor layers or chips to a receiving substrate for many applications, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 293 publications
(444 reference statements)
0
13
0
Order By: Relevance
“…The total processing time of this strategy is less than ≈20 s, which is 2–3 orders of magnitude more efficient compared to the CLO method (which normally takes a few hours or a few days) at sample areas close to the wafer level. [ 13 ] Although the current mechanical release method only takes a few seconds, [ 19 ] it inevitably requires a tedious sacrificial layer growth process to weaken the bond between the substrate and the film. In our strategy, it only requires one‐step laser scanning for the separation of GaN film, effectively simplifying the fabrication process of GaN‐based devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total processing time of this strategy is less than ≈20 s, which is 2–3 orders of magnitude more efficient compared to the CLO method (which normally takes a few hours or a few days) at sample areas close to the wafer level. [ 13 ] Although the current mechanical release method only takes a few seconds, [ 19 ] it inevitably requires a tedious sacrificial layer growth process to weaken the bond between the substrate and the film. In our strategy, it only requires one‐step laser scanning for the separation of GaN film, effectively simplifying the fabrication process of GaN‐based devices.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17,18 ] Among these approaches, LLO is favored by the industrial field because of its pollution‐free, stable, and convenient integration characteristics for removing a GaN layer from a sapphire substrate and then transferring the GaN layer onto a potential foreign substrate. [ 19 ] In Table 1 , the recent studies using LLO process for separation of GaN layer from sapphire substrate have been benchmarked and concluded. Normally, excimer lasers and nanosecond ultraviolet lasers are used for the LLO process because the photon energy of these two sources is larger than the bandgap of GaN but less than the bandgap of sapphire.…”
Section: Introductionmentioning
confidence: 99%
“…For conventional LEDs, mechanical bending during operation induces strain and potential self-heating, causing a degradation in the device performance, which may limit the utilization of μLEDs in flexible substrates. ,, In 2020, Asad et al demonstrated several intermediary metal bonding layers and developed a “paste-and-cut” technique to transfer GaN μLEDs from sapphire substrates to flexible platforms. They also investigated the effect of LED geometry on the performance of the flexible devices.…”
Section: Emerging Applications Of μLedsmentioning
confidence: 99%
“…The development of techniques that can transfer LED chips from the growth substrate to another substrate is of great importance, which is driven by a few primary considerations. [117,118] The first driving force is to improve the LED optical performance and thermal stability. This is particularly true for general lighting, where high-power LEDs must be used.…”
Section: Chip Mass Transfermentioning
confidence: 99%